2007
DOI: 10.1523/jneurosci.2786-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Reversible GABAAReceptor Plasticity after Ethanol Intoxication

Abstract: The time-dependent effects of ethanol (EtOH) intoxication on GABA A receptor (GABA A R) composition and function were studied in rats. A cross-linking assay and Western blot analysis of microdissected CA1 area of hippocampal slices obtained 1 h after EtOH intoxication (5 g/kg, gavage), revealed decreases in the cell-surface fraction of ␣4 and ␦, but not ␣1, ␣5, or ␥2 GABA A R subunits, without changes in their total content. This was accompanied (in CA1 neuron recordings) by decreased magnitude of the picrotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
211
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(245 citation statements)
references
References 76 publications
32
211
2
Order By: Relevance
“…The δ-GABA A Rs, sometimes called the "one-glass-of-wine" receptors (24), are located in several brain regions, including the thalamus, cerebellum, hippocampus, and striatum (25,26), and show high sensitivity to relatively low doses of ethanol (2)(3)(4)(5)(6)(7)(8)27). A number of previous studies demonstrate the involvement of δ-GABA A Rs in a range of ethanolinduced functional effects, including ataxia, sedation, and reward (2-8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The δ-GABA A Rs, sometimes called the "one-glass-of-wine" receptors (24), are located in several brain regions, including the thalamus, cerebellum, hippocampus, and striatum (25,26), and show high sensitivity to relatively low doses of ethanol (2)(3)(4)(5)(6)(7)(8)27). A number of previous studies demonstrate the involvement of δ-GABA A Rs in a range of ethanolinduced functional effects, including ataxia, sedation, and reward (2-8).…”
Section: Discussionmentioning
confidence: 99%
“…Further, knockdown of δ subunit expression in the medial shell of the nucleus accumbens reduces alcohol intake in rats (6). Finally, overstimulation and subsequent internalization of α4βδ extrasynaptic GABA A Rs after persistent stimulation by ethanol seem to underlie the development of rapid tolerance to the ataxic effects of ethanol (4).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Biochemical studies have demonstrated that the α4 and δ subunits are often present in the same receptor complex (Sur et al, 1999). Furthermore, α4βδ receptor expression has been shown to be very plastic in the CNS, with α4 protein levels subject to rapid regulation after administration of GABAergic drugs (Birzniece et al, 2006;Liang et al, 2007).…”
Section: Behavioural Phenotype Of Fmr1 Knockout Micementioning
confidence: 99%